Studies on Combining Ability and Heterosis for Yield, Yield Contributing Traits in Rice (Oryza sativa L.) Hybrids - Harshitha, D.; Srikanth, T.; Madhukar, P.; Ratnakar, V. (International Journal of Bio-resource and Stress Management, 2025)
The study was conducted during kharif (July-November, 2023) and rabi (December-March) 2023–24 at regional agricultural research station in polasa, Jagtial, Telangana, India to investigate general combining ability, specific combining ability and standard heterosis in rice. Twenty hybrids were developed during kharif season by crossing four CMS lines with five restorers using a line×tester mating design and later, during rabi (December-March) 2023–24, parents, hybrids and checks were evaluated using a RBD with three replications. Among the lines, JMS 24B exhibited promising performance as a general combiner for yield and related traits. Among the testers, the testers IR-23352-7R, KNM-7660 and IR 10198-66-2R displayed significant positive gca effects for yield and related traits were considered as best general combiners. Among the crosses, JMS 13A×IET-23993, CMS 59A×KNM 7660 and JMS 24A×RP-4516-3-6 were exhibited as best specific combining ability for yield and related traits. Of 20 hybrids, JMS 24A×IR-10198-66-2R had highest significant standard heterosis for yield over the JGL-24423 and KPH-473 checks. The highest significant standard heterosis for plant height was observed RMS 1A×RP 4516-3-6, JMS 13A×RP 4516-3-6 and JMS 24A×RP 4516-3-6, compared to the JGL 24423 and KPH-473 checks. RMS 1A×KNM 7660, RMS 1A×IR 10198-66-2R, and CMS 59A×KNM 7660 exhibited the highest significant standard heterosis for number of productive tillers plant-1. These hybrids showing strong heterotic expression in F1 generations can contribute to the identification of superior segregants in future generations.